General control non-derepressible 2 (GCN2) in T cells controls disease progression of autoimmune neuroinflammation - Keil, Melanie; Lanz, Tobias; Wick, Wolfgang; Platten, Michael (Journal of neuroimmunology, 2016)
Relapsing-remitting multiple sclerosis (MS)22MS: multiple sclerosis. is characterized by phases of acute neuroinflammation followed by spontaneous remission. Termination of inflammation is accompanied by an influx of regulatory T cells (Tregs).33Tregs: regulatory T cells. The molecular mechanisms responsible for directing Tregs into the inflamed CNS tissue, however, are incompletely understood. In an MS mouse model we show that the stress kinase general control non-derepressible 2 (GCN2),44GCN2: general control non-derepressible 2. expressed in T cells, contributes to the resolution of autoimmune neuroinflammation. Failure to recover from acute inflammation was associated with reduced frequencies of CNS-infiltrating Tregs. GCN2 deficient Tregs displayed impaired migration to a CCL2 gradient. These data suggest an important contribution of the T cell stress response to the resolution of autoimmune neuroinflammation.
Gesehen am 21.03.2018